2015
DOI: 10.1093/cid/civ296
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid-Lowering Effect of Tenofovir/Emtricitabine: A Randomized, Crossover, Double-Blind, Placebo-Controlled Trial

Abstract: NCT01458977.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
65
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 23 publications
14
65
2
2
Order By: Relevance
“…At weeks 24 and 48, there were small, statistically significant differences in increases in total cholesterol, LDL cholesterol, and HDL cholesterol for participants receiving TAF compared with those receiving TDF, but no difference in the TC:HDL ratio, which is associated with cardiovascular risk (Deeks et al, 2013, Wilson et al, 1998, D'Agostino et al, 2008, Goff et al, 2014). These findings are consistent with what has been seen in other TAF vs TDF studies (Sax et al, 2015, Mills et al, 2015, Wohl et al, 2016) and are thought to be due to greater plasma TFV concentrations with TDF (Wohl et al, 2016, Tungsiripat et al, 2010, Santos et al, 2015, Mulligan et al, 2013, Behrens et al, 2012, Patel et al, 2014). Traditional lipid panels may underestimate cardiovascular risk in HIV-infected individuals, (Munger et al, 2015) and there is growing appreciation that pro-inflammatory lipids may contribute to immune activation in persons infected with HIV, including oxidized LDL, as levels of oxidized LDL have been associated with levels of sCD14 in this population (Zidar et al, 2015, Hileman et al, 2016, Nou et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…At weeks 24 and 48, there were small, statistically significant differences in increases in total cholesterol, LDL cholesterol, and HDL cholesterol for participants receiving TAF compared with those receiving TDF, but no difference in the TC:HDL ratio, which is associated with cardiovascular risk (Deeks et al, 2013, Wilson et al, 1998, D'Agostino et al, 2008, Goff et al, 2014). These findings are consistent with what has been seen in other TAF vs TDF studies (Sax et al, 2015, Mills et al, 2015, Wohl et al, 2016) and are thought to be due to greater plasma TFV concentrations with TDF (Wohl et al, 2016, Tungsiripat et al, 2010, Santos et al, 2015, Mulligan et al, 2013, Behrens et al, 2012, Patel et al, 2014). Traditional lipid panels may underestimate cardiovascular risk in HIV-infected individuals, (Munger et al, 2015) and there is growing appreciation that pro-inflammatory lipids may contribute to immune activation in persons infected with HIV, including oxidized LDL, as levels of oxidized LDL have been associated with levels of sCD14 in this population (Zidar et al, 2015, Hileman et al, 2016, Nou et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with TDF‐containing regimens has consistently been associated with lower lipids compared with non‐TDF‐containing regimens, an effect thought to be a dose‐related effect of plasma tenofovir on reducing select lipid parameters 15, 16, 17, 18. The changes in fasting lipids seen in Study 1216 are consistent with differences seen in treatment‐naïve patients as well as in other studies evaluating the switch to TAF from TDF while maintaining other antiretroviral regimen components 4, 5.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with TDF has consistently been associated with lower lipids compared with other regimens in treatment-naive or virologically suppressed individuals. 22,23 This TDF lipid effect is thought to be associated with the plasma level of TFV. 22,24 In this study, participants switching from TDF-containing regimens showed increases in total, high, and low-density lipoprotein cholesterol and triglycerides, likely related to the significant reductions in plasma TFV concentrations.…”
Section: Discussionmentioning
confidence: 99%